Fitoremediasi Logam Berat Kadmium (Cd) - Nur, Fatmawati (Jurusan Biologi UIN Alauddin Makassar, 2013)
Phytoremediation consists in treating environmental pollutions through the use of plants and their associated microbes. Phytoremediation can be used for pollutant stabilization, extraction, degradation or volatilization. Cadmium is one of the most toxic trace metallic elements for living organisms and its accumulation in the environment is recognized as a worldwide concern. Plants suitable for efficient pollutant extraction from the soil should combine different characteristics like fast growth, high biomass, high tolerance and high accumulation capacities in harvestable parts. Several studies haveshown that plants can accumulate Cd in the body such as Eichornia crassipes, Brassica napus, Avicenna marina, Lycopersicon esculentum, Wolffia globosa, Phytolacca Americana, Solanum nigrum, Typha domingensis, Sedum plumbizincicola, Thlaspi caerulescens, Helianthus annuus,Lolium perenne, Tagetes erecta, Chara australis, Jatropha curcas, Sedum alfredii, Atriplex halimus,Phragmites cummunis, Nitella opaca, Phragmites australis, Typha angustifolia, Cyperus esculentus, Chara aculeolata, Ricinus communis, Hibiscus cannabinus, Zea mays, Arabidopsis halleri, Arundo donax, and Vetiveria zizanioides.Keywords: Cadmium, Phytoremediation, Plant